PATH-01. Infant-Type Hemispheric Glioma: New Molecular Alterations and Precision-Medicine Treatment. (3rd June 2022) - Hu, Wanming; Yuan, Li; Zeng, Jing
Abstract: BACKGROUND: Infant-type hemispheric glioma, harboring alterations in the receptor tyrosine kinases ALK, ROS1, NTRK and MET, is a new subtype of Pediatric-type diffuse high-grade gliomas in the 2021 WHO classification of CNS tumors. It has important clinical therapeutic value with specialized therapeutic drugs. Here, we presented 3 cases of infant-type hemispheric glioma. Patient1 with EML4-ALK fusion which often appeared in lung cancer, the other 2 patients have new molecular alterations which has not been reported before (Patient2 has both NTRK1-TP53/TP53-NTRK1 fusions and p53 protein showed characteristic cytoplasm positive; Patient3 presented a brand-new ALK-QKI fusion combined with ALK mutation and focal SMARCB1 deletion. All these 3 cases received corresponding targeted therapy and have a good recovery and normal neurologic function till now. METHOD: Immunohistochemistry, fluorescent in situ hybridization and whole-transcriptome sequencing. RESULTS: Case 18 months, male, right semiovale center occupation. Histopathology: High-grade neuroepithelial neoplasm. IHC: GFAP(only few cells+), Olig2(-), S100(+), CD56(+), Syn(-), NSE(focal+), NeuN(-), CD34(-), INI-1(+), Ki67(10%+). Characteristic Molecular Information: EML4-ALK fusion. Follow-up: 15 months, alive. Case 2: 3 years, female, insular lobe occupation.Histopathology: Gliosarcoma. IHC: GFAP(partly+), Olig2(partly+), Vimentin(+), P53(cytoplasm+), pan-TRK(+), Ki67(25%+). Reticular fiber staining showed biphasic tissue pattern with reticulin-rich sarcomatous and reticulin-free gliomatous elements. Characteristic Molecular Information: NTRK1-TP53 and TP53-NRTK1 fusion. Follow-up: 27 months, alive. Case 3: 3 years, male, left parietal occipital lobe occupation. Histopathology: GBM and AT/RT. IHC: GFAP(partly+), Olig2(partly+), INI-1(partly-), BRG1(+), SYN(-), CD34(-), BRAF(-), S100(-), CK(-), H3K27M(-), IDH1(-), P53(40%+), ATRX(+), pan-TRK(-), ALK(+), Ki67(30%+). Characteristic Molecular Information: ALK mutation, ALK-QKI fusion, RAD51C mutation and focal SMARCB1(INI-1) deletion. Follow-up: 14 months, alive. CONCLUSION: Infant-type hemispheric glioma is a special kind of glioma, which is particularly suitable for precision-medicine treatment approaches. Their overall survival is good compared with other three pHGG subtype.